Knee hemangioma - Diagnostic dilemma: A case report - Sharma, Mohit; Barupal, Sukhram (Indian Journal of Case Reports, 2018)
A hemangioma is a benign tumor of the endothelial cells that line the blood vessels. It is characterized by an increased number of normal or abnormal vessels filled with blood. Usually, it presents as a painful or painless swelling in extremities. Surgical excision is the treatment of choice for large excisable tumor. Here, we present the case of a young girl, referred to our department by orthopedician with a complaint of painful swelling below the right knee that was gradually increasing in size for the past 7 years. Initially, it was misdiagnosed as a hematoma. Hence, incision and drainage were tried but unsuccessful. Finally, computed tomography angiography showed that it was a vascular structure like the hemangioma. The aim of presenting this case is to create awareness and acknowledge the possibility of a hemangioma arising from a joint is usually rare, but it should be kept as a differential diagnosis.